Distributed Control of Discrete-Time Linear Multi-Agent Systems With Optimal Energy Performance - Huang, Guan; Zhang, Zhuo; Yan, Weisheng (Frontiers in Control Engineering, 2022)
This paper investigates the leader-based distributed optimal control problem of discrete-time linear multi-agent systems (MASs) on directed communication topologies. In particular, the communication topology under consideration consists of only one directed spanning tree. A distributed consensus control protocol depending on the information between agents and their neighbors is designed to guarantee the consensus of MASs. In addition, the optimization of energy cost performance can be obtained using the proposed protocol. Subsequently, a numerical example is provided to demonstrate the effectiveness of the presented protocol.